Modern Foreign Approaches to Open Adoption - Y.F. Chinareva (Современная зарубежная психология)
Context and relevance. The article presents a review of foreign literature on open and closed adoption, presents the results of studies that have not previously been translated into Russian, which explore various aspects of an adopted child's personality development through the lens of open and closed adoption models. The foreign experience of the development of open adoption is considered using the example of Great Britain, where a closed model was in effect until 1975. The article analyzes different approaches taken by foreign researchers in understanding the challenges of open adoption, its distinctions from the traditional closed model, and discusses concerns about potential risks of open adoption — particularly the possibility that it may hinder the formation of close familial bonds within the adoptive family. The author proposes an original classification of open adoption types based on the intensity of contact between adoptive and birth families and explains the difference between open adoption and adoption without secrecy. The article holds practical value for the general public, adoptive parents, and professionals in the field of child protection services, as it helps to clarify the practical aspects of open and closed adoption models from the perspective of the adopted child's best interests.